(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Uterine prolapse is a type of pelvic organ prolapse where the supporting pelvic structures of the uterus weakens and result in the descent of the uterus from its normal position. This condition may arise from the gradual failure of the supporting and suspensory structures of the uterus and vaginal wall over time. Most important conservative management involves pelvic floor exercises. When conservative management fails, surgery is the only treatment option. Yonirogas which show features of pelvic organ prolapse are Prasramsini, Andini, Phalini, Mahayoni and Vatiki. Among them, Prasramsini can be most suitably correlated with 1st and 2nd degree uterine prolapse[1]. The management principle of pelvic organ prolapse includes Vathika yoni roga chikitsa along with Sthanika chikitsa. Treatment mainly aims at Vathasamana, Brimhana, Sandhana, Balya and strengthening of pelvic floor musculature. This case report explores the add-on effect of Sthanika chikitsa particularly Yoni abhyanga, Yoni pichu dharana and Matra vasti with Dhanwantharam thailam and Avagaha with Dasamoola kwatha in second degree uterine prolapse with standard conservative management, pelvic floor exercise. Symptomatic relief and functional improvements were observed after 3 months of combined therapy, suggesting the additive benefits of integrating Sthanika chikitsa into standard conservative management.